Peran Kegiatan Upacara Bendera Dalam Menanamkan Nilai Nasionalisme Pada Anak Usia Dini Di Ra Darussalam - Hanis Adira Lubis; Padilah Hasan; Nur Hamni; Nikmah Khairani (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
Instilling Nationalist Values ​​in carrying out the flag-raising ceremony is an important step in cultivating and strengthening the feeling of love for the homeland and national spirit among the younger generation, especially at the Early Childhood stage. Early Childhood is a child whose age range is 0-6 years, where this period is very important in providing stimulation for optimal growth and development of children. This research aims to instill the values ​​of Nationalism in Early Childhood through Flag Ceremony activities at Ra Darussalam. This research uses descriptive qualitative methods. Data collection techniques use observation, interviews and documentation. Based on the research results, it can be seen that the role of ceremonial activities can instill Nationalist Values ​​in children.